Charles L. Scott papers - Scott, Charles L. (Charles Lewis), 1883-1954.
Correspondence, memoranda, speeches, reports, articles, orders, photographs, and other papers pertaining chiefly to Scott's role as a military tactician, his World War II military service, and the development and employment of mechanized armored units in World War II. Includes material pertaining to the U.S. Army 2nd Armored Division, organized by Scott; his command of the Armored Replacement Training Center (ARTC) at Fort Knox, Kentucky; and the North African campaigns of World War II.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army. -- Armored Division, 2nd.; United States. -- Army -- Armored troops; Armored Replacement Training Center (Fort Knox, Ky.); Mechanization, Military; Military art and science; Tactics; World War, 1939-1945.; World War, 1939-1945 -- Tank warfare; World War, 1939-1945 -- Campaigns -- Africa, North; Army officers